The princess who stole his heart - Danvers, Julie (Harlequin medical romance, 2023)
From paradise fling... to royal revelation! When doctor Princess Danielle takes a fellowship in the Caribbean, she's swept off her feet by a bronzed god -- cardiologist Cade. But her title is a secret... and a relationship with Cade strictly forbidden! Cade has shut the door on romance, and yet his attraction to Dani is undeniable. After finally surrendering to his desire, he fears Dani might steal his locked-up heart -- especially when she reveals that their passion has had a shocking royal consequence!